HUBUNGAN PENGETAHUAN BAHAN MAKANAN DAN KELENGKAPAN FASILITAS PRAKTEK DENGAN HASIL BELAJAR PENGOLAHAN DAN PENYAJIAN MAKANAN KONTINENTAL DI SMK NEGERI 3 PEMATANGSIANTAR - Hanum, Yuspa; Siregar, Efrida Elisa (JURNAL KELUARGA SEHAT SEJAHTERA, 2017)
ABSTRACTThis study aims to determine: (1) Knowledge of foodstuffs; (2) Completion of practice facilities; (3) The learning result of processing and serving of continental food; (4) The relationship of food knowledge with the learning result of processing and serving of continental food; (5) The relation of the completeness of the practice facility to the learning result of processing and serving of continental food; (6) Knowledge relation of foodstuffs and completeness of practice facility with learning result of processing and presentation of continental food. Based on the results of the research indicate that: (1) the level of knowledge of student's food trend of 64.86% is in enough category; (2) The trend level of the completeness of the practice facility of 56.76% is in sufficient category; (3) The level of trends in the learning outcomes of processing and serving of continental food is in the high category in terms of School Standard Assessment and Minimum Criteria of Completeness; (4) The result of partial correlation analysis there is a positive and significant correlation between the knowledge of foodstuff with the learning result with value (ry.1.2 = 0,345> rt = 0,325; 5%); (5) The result of partial correlation analysis there is a positive and significant correlation between the completeness of practice facility with learning result with value (ry.2.1 = 0,332> rt = 0,325; 5%); (6) Based on multiple correlation test there is a positive and significant relationship between the knowledge of foodstuffs and the completeness of practice facilities with learning outcomes with value R = 0.345 so that obtained Ftabel = 3.28 and Fh = 3.39 where Fcount> Ftable (3.39 > 3.28) so that the coefficient of double correlation at significant level 5% means.  Keywords : Knowledge Of Foodstuff, Completeness Of Practice Facility, Processing And Presentation Of Continental Food